PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Survei pada pengguna sepeda motor Honda Beat di Kota Tasikmalaya) - Shintya Nisawaty; Ari Arisman; Kusuma Agdhi Rahwana (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
This study aims to determine the effect of simultaneous and partial of Purchase Decisions in terms of brand image, and product quality on purchasing decisions for Honda Beat motorcycles in Tasikmalya city. The research method used in this study is a quantitative method with a survey approach. The population studied were 100 respondents. Analysis of the data in this study using Multiple Regression Analysis using SPSS version 26 software. The results showed that brand image and product quality simultaneously influenced the purchase decision of Honda Beat motorcycles in the city of Tasikmalya. Brand image partially influences the purchase decision of Honda Beat motorcycles in the city of Tasikmalya. Product quality partially has a significant effect on purchasing decisions for Honda Beat motorcycles in the city of Tasikmalya. Product quality partially has a significant effect on purchasing decisions for Honda Beat motorcycles in the city of Tasikmalaya.